Investigation of Etiologic Agents and Clinical Presentations of Otomycosis at a Tertiary Referral Center in Tehran, Iran - Hasti KAMALI SARWESTANI; Roshanak DAIE GHAZVINI; Seyed Jamal HASHEMI; Sassan REZAIE; Mohsen GERAMI SHOAR; Shahram MAHMOUDI; Miad ELAHI; Ardavan TAJDINI (Tehran University of Medical Sciences, 2019)
Background: Otomycosis is a superficial infection of the ear caused by a spectrum of various fungal agents and its epidemiology depends on geographical region and climatic condition. The aim of this study was to investigate the causal agents and clinical manifestations of otomycosis at a tertiary referral center in Tehran, Iran. Methods: From Apr 2016 to Jan 2017 a set of 412 subjects with suspicion of external otitis were included. Clinical examination and specimen collection were performed by an otorhinolaryngologist. Subsequently, direct examination and culture were performed on specimens and isolated molds were identified morphologically. Yeast isolates were identified using CHROMagar Candida medium and PCR-RFLP of ribosomal DNA whenever needed. Data were analyzed using SPSS. Results: Otomycosis was confirmed in 117 cases (28.39%) including 64 (54.7%) males and 53 (45.3%) females. Patients were within the age range of 10-75 yr and the highest prevalence was found in the age group of 46-55 yr (30.77%). Pruritus (89.74%) and auditory manipulation and trauma (83.76%) were the predominant symptom and predisposing factor, respectively. Among 133 isolates from 117 patients, Aspergillus niger (n=50, 37.59%) was the most common etiologic agent and Candida glabrata (n=25, 18.8%) was the predominantly isolated yeast. Furthermore, 16 cases of mixed infection were identified and coinfection due to A. niger and C. glabrata (seven cases) was the predominant pattern. Conclusion: Our results revealed the high prevalence of C. glabrata and mixed infections in otomycosis patients. Therefore, mycological examinations should be considered for proper treatment.